Antecedents and consequences of social network characteristics for expatriate adjustment and performance in overseas assignments: implications for HRD - Osman-Gani, AAhad M.; Rockstuhl, Thomas (SAGE Publications, 2008)
In this conceptual article, the literature on expatriate social network and its relationships to adjustment and performance in overseas assignments have been reviewed exhaustively. By identifying some gaps and inconsistencies found in the literature, a typology of research on expatriate network explanations has been proposed based on whether the aim is to explain performance variation or adaptation to local practices and norms, and also whether their explanatory mechanism is based on the structure or resources of the network. Specific propositions for each of the four resulting approaches have been developed. It has also been recommended that future researchers should study antecedents of social network structure because of their relevance to HRD interventions. The implications for HRD research and practice have been discussed at the end.